2004
DOI: 10.1111/j.1468-0106.2004.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Reporting errors, ability heterogeneity, and returns to schooling in China

Abstract: This study is aimed at providing a more accurate estimate of the returns to schooling in China by controlling for unobserved ability heterogeneity and measurement errors. We identify a unique instrument to correct for the omitted ability bias. We find that the attenuation bias caused by measurement error dominates the omitted ability bias in the OLS estimation. Based on the GMM estimation, for young workers in China, the return to schooling is 15.0% overall and 16.9% for women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 27 publications
2
34
0
Order By: Relevance
“…Chen and Hamori, 2009;Trostel et al, 2002;Arabsheibani and Mussurov, 2007) have utilized spousal education as an IV, while some have utilized parental education (e.g. Flabbi et al, 2008;Gao and Smyth, 2011;Heckman and Li, 2004;Li and Luo, 2004;Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Chen and Hamori, 2009;Trostel et al, 2002;Arabsheibani and Mussurov, 2007) have utilized spousal education as an IV, while some have utilized parental education (e.g. Flabbi et al, 2008;Gao and Smyth, 2011;Heckman and Li, 2004;Li and Luo, 2004;Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Liu, Hammitt and Lin (2000) estimate a wage equation for Taiwanese and find that the effect of father's schooling on wages is larger than the effect of mother's schooling -a university-educated father is associated with a 15% wage advantage compared with an illiterate father in the private sector. Li and Luo (2004) study the case of China and find that father's education is significant in affecting children's wages but mother's education is not significant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The CHIP dataset is also nationally representative and has been widely used in the literature as it is more accessible to the research community compared to NBS datasets (Li and Luo, 2004;Fleisher et. al., 2004).…”
Section: Data and Sample Statisticsmentioning
confidence: 99%
“…Researchers have generally used the IV method (see e.g. Li and Luo 2004) to isolate the causal effect of education on earnings. Thus, for example, Fersterer and Winter-Ebmer (2003) use information on whether the individual smokes at age 16 or not to help differentiate between the effects of education and ability.…”
Section: The Data and Model Specificationmentioning
confidence: 99%
“…The availability of CHIP 1995 data makes it possible to construct instrumental variables (IV) for alternative estimations. Li and Luo (2004) used the CHIP 1995 data and applied various IV estimations to estimate returns to schooling for young workers (aged 30 or under in 1995) in urban China. Their results indicated that the returns to education are considerably higher than those obtained from the use of OLS.…”
Section: Literature Reviewmentioning
confidence: 99%